The Effectiveness of Talking Stick Method in Teaching Speaking - Sitti Fitriawati (Sintuwu Maroso Journal of English Teaching, 2017)
This study aimed to find out the effectiveness of Talking Stick Method in teaching speaking at second semester students of FKIP UNSIMAR Poso. This research is pre-experimental design (One Group Pretest Posttest). The techniques of data collection are interview and multiple choices written tests. The population of this study is 37 students and the sample is 19 students. The results are discussed furthermore.Keywords: Talking stick method, Teaching speaking, Effectiveness